STRATEGI PEMASARAN PENDIDIKAN DENGAN MENGGUNAKAN MEDIA DIGITAL DALAM MENINGKATKAN KUANTITAS PESERTA DIDIK - Rizka Maturidi; Nugraha, Doni; Amarullah Malik (Program Studi Manajemen Pendidikan Islam, 2024)
Digital media in marketing educational services is a form of technological development so that the dissemination of information becomes wider. With competition between institutions, institutions need to develop effective marketing strategies, one of which is by utilizing technological developments, namely digital media. This research was conducted to describe and analyze the use of digital media as a means of marketing educational services at MTs Riyadlushshorfiyah. The research method used in this research is qualitative using interviews, observation and document study methods to collect data. In this study, the data source was obtained from respondents, namely the head of the madrasah, the Head of TU and the Operator. This research data was collected using three methods, namely interviews, observation and documentation. To test the credibility of the data, this research uses source triangulation. Then the data obtained will be processed by data condensation, data presentation and drawing conclusions. The results of research on the use of digital media as a means of marketing educational services are (1) the implementation of educational marketing strategies at MTs Riyadlushshorfiyah including planning and objectives. (2) Implementation of the use of digital media as a means of marketing educational services in accordance with the five aspects of the promotional mix and social media trends. (3) The success in using digital media as a means of marketing educational services at MTs Riyadlushshorfiyah is that the number of new students is increasing from year to year and gaining a wider market